PANJANG MULUD SEBAGAI BUDAYA DAN KESENIAN TRADISI ISLAM DI KOTA SERANG – BANTEN - Rosid, Abdul (Jurnal Ilmu Pendidikan Muhammadiyah Kramat Jati, 2023)
A distinctive characteristic of the artistic culture found in Banten is Panjang Mulud, which is celebrated to commemorate the birth of Prophet Muhammad, where there are several series of events and ornaments that are part of Panjang Mulud. This study discusses several issues, namely the History of Panjang Mulud in Banten, Evidences of the Prophet's Birthday Celebration, Implementation of Panjang Mulud in the city of Serang, Supporting Activities of Panjang Mulud, Benefits of Implementing Panjang Mulud, Distinctive Characteristics of Local Wisdom in Panjang Mulud in the city of Serang, Differences between Past and Present Panjang Mulud Celebrations, Differences in Celebrations in Each Subdistrict in the city of Serang. The purpose of this study is to understand the implementation of the Prophet's Birthday Celebration in the city of Serang, Banten Province, as well as to comprehend the meaning of the Prophet's Birthday celebration so that it can be taken as a lesson and add a religious aspect to practicing the religion. The results of this study explain the origins of Panjang Mulud, one of which was pioneered by Syech Nawawi Al-Bantani in resistance against colonization in Banten, as well as providing evidence for the celebration of the Prophet's birthday, one of which is Surah Yunus verse 58, and the supporting factors of this celebration include the series of remembrance (dzikir) of saman, terbang gede, and rudat. This celebration has been beneficial both economically and socially. As a distinctive feature, the Panjang Mulud celebration includes egg-shaped flower ornaments. The conclusion of this study is that in conducting Panjang Mulud, the community of Serang has its own distinct characteristics in each of the six subdistricts in the city, and the series of events and ornaments also follow the development of the times.